2015
DOI: 10.1183/13993003.02139-2014
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the complexity of COPD by microRNAs: it's a small world after all

Abstract: Chronic obstructive pulmonary disease (COPD) is a progressive lung disease and is currently the fourth leading cause of death worldwide. Chronic inflammation and repair processes in the small airways are characteristic of COPD. Despite extensive efforts from researchers and industry, there is still no cure for COPD, hence an urgent need for new therapeutic alternatives. MicroRNAs are such an option; they are small noncoding RNAs involved in gene regulation. Their importance has been shown with respect to maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 69 publications
(108 reference statements)
3
62
0
Order By: Relevance
“…In vitro and in vivo studies have shown that miRNAs play a crucial role in cellular response to stress as well as cell growth and death 35, 36, 49, 50 . The airway epithelial miRNA transcriptome changes in response to cigarette smoke exposure 35, 49 , and miRNAs have been implicated in COPD pathology 35, 49, 51 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro and in vivo studies have shown that miRNAs play a crucial role in cellular response to stress as well as cell growth and death 35, 36, 49, 50 . The airway epithelial miRNA transcriptome changes in response to cigarette smoke exposure 35, 49 , and miRNAs have been implicated in COPD pathology 35, 49, 51 .…”
Section: Discussionmentioning
confidence: 99%
“…The airway epithelial miRNA transcriptome changes in response to cigarette smoke exposure 35, 49 , and miRNAs have been implicated in COPD pathology 35, 49, 51 . A main goal of this study was to determine the global effects of eCig exposure upon miRNA expression, and test whether miRNAs alter expression of their target mRNA in eCig-exposed lung epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The major function of both the up- and down-regulated miRNAs was inflammation, with several targets associated with NF-κB pathway. There are other examples of miRNAs related to cigarette smoke and inflammation considered to be involved in COPD, such as effects in smooth muscle, fibroblasts, macrophages and neutrophils, and specific miRNA changes in bronchial epithelia of smokers versus non-smokers (97, 116). …”
Section: Introductionmentioning
confidence: 99%
“…BAKER et al [94] postulate that the reduced expression of both Sirtuins is regulated by the microRNA MiR-34a, a small endogenous noncoding RNA, which appears to be increased in COPD patients compared to controls. Although the role of microRNAs in COPD has been extensively reviewed [96] the role of microRNAs in accelerated lung ageing is not extensively investigated and remains rather elusive [97].…”
Section: Epigenetic Changesmentioning
confidence: 99%